Evaluasi Penerapan Pengendalian Intern Atas Pelaporan Keuangan Di Lembaga Penjaminan Mutu Pendidikan (LPMP) Provinsi Kalimantan Barat - B2092191011, Sri Rahayu (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2021)
This thesis aims to evaluate the implementation of internal control including elements of the control environment, risk assessment, control activities, information and communication and monitoring carried out in LPMP of West Kalimantan Province. This research uses qualitative methods, data collection techniques with interviews, observation and study documentation, triangulation techniques are carried out to ensure the validity of the data.The results showed that internal control in LPMP West Kalimantan Province has generally been implemented properly according to regulations. However, a mechanism is needed to anticipate, identify and react to changes that have a major impact on the institution. In addition, written procedures need to be formulated as a guide in the implementation of internal control monitoring.